Wide-field full-Stokes polarimetry for conical light based on all-dielectric metasurface - Qing Luo; Xiaoshao Ma; Yang Guo; Yang Zhou; Junwei Ma; Weihao Yang; Longjiang Deng; Lei Bi; Jun Qin (Journal of Materiomics)
Polarization camera based on CMOS sensor and nano wire-grid technology have found widespread applications in medical diagnostics, remote sensing and industrial inspection. However, the limited filtering properties of wire-grid polarizers and the small field-of-view provided by conventional microlens restrict the energy efficiency of these systems while also increasing their cost, size and weight. In this study, we propose an innovative approach that integrates focusing and splitting of polarization states into a single-layer all-dielectric metasurface. This metasurface enables full-Stokes polarization imaging for a wide field-of-view conical light. The design of the metasurface utilizes a phase compensation method to effectively focus orthogonal polarized conical light onto the central pixel of the CMOS sensor. Theoretical analysis demonstrates that this metasurface can accurately detect full-Stokes parameters within ±20° incident cone angles with an average efficiency reaching 83.0%. The angle can be extended to ±90° with an average efficiency exceeding 80%. We fabricated a three super-pixel metasurface prototype, and experimental measurements reveal its ability to efficiently focus and split three pairs of orthogonal polarization states under ±11° conical angle incidence with an average focusing efficiency of 68.1%. This study presents a promising solution for achieving wide field-of-view and high-efficiency polarization detection in integrated CMOS systems.